Pengaruh Kualitas Layanan Dan Kemudahan Penggunaan Terhadap Kepuasan Konsumen Generasi Milenial Di Platform Tokopedia - Lafreda Nanda Wibowo; Widarto Rachbini (Journal Economic Excellence Ibnu Sina, 2024)
This study aims to analyze the effect of service quality and ease of use on millennial consumer satisfaction on the Tokopedia e-commerce platform. Along with the development of technology, e-commerce has become the main choice for consumers because of its convenience, accessibility, and ease of use. This study uses a quantitative method with a survey approach by distributing online questionnaires to respondents who meet demographic criteria, with a purposive sampling technique. Data analysis was carried out using SPSS, including normality tests, ANOVA, and coefficient analysis to measure the effect of service quality and ease of use on consumer satisfaction. The results of the study show that both variables have a positive and significant effect on consumer satisfaction, so that improving service quality and ease of use is an important strategy in building customer loyalty in the digital era.